PENAMBAHAN JENIS DAN LEVEL BAHAN PENGISI YANG BERBEDA TERHADAP NILAI PROFIL WARNA L*, a*, b* PRODUK CHIP TELUR - K. Kartina; N Nahariah; H. Hikmah (Jurnal Ilmu dan Teknologi Peternakan, 2022)
Egg chips are not yet common in society so it is necessary to pay attention to appearance, especially color. Color is one of the determinants of food being accepted or not by consumers. This study aims to determine the effect of adding the type and level of fillers to the value of L*, a*, and b* in egg chips. Eighty-one eggs were used in the research. The studies were arranged based on a completely randomized design with a 3 x 3 factorial pattern with 3 replications. The first factor consisted of 3 types of fillers, namely tapioca powder, soybean protein isolate, and Porang powder. The second factor was the level of filler (%) 3, 6, and 9 respectively. Parameters measured were color (L*= brightness level, a*= redness level, b*= yellowness level). The addition of tapioca powder can increase the brightness of the egg chips, and Porang powder can increase the reddish and yellowish color of the egg chips. However, at the filler level, it can increase the color of the brightness, redness, and yellowness of egg chips.